Unilateral asterixis due to a lesion of the ventrolateral thalamus. Issue 7 (July 1994) - Stell, R; Davis, S; Carroll, W M
Abstract : A case of unilateral asterixis in a man with a focal ischaemic lesion of the contralateral ventral thalamus is presented. Atypically, the movements were present at rest and had a pattern of activation that resulted in an initial misdiagnosis of epilepsia partialis continua. This case emphasises the importance of electromyographic analysis in establishing the correct diagnosis of involuntary movements before starting specific treatment.